The Subject Between Grammatical And Pragmatic Features In The Arabic Language - bouchelig, ouahiba (El Omda in Linguistics and Discourse Analysis, 2022)
In this research, we discuss the most important grammatical and pragmatic features of the subject in the Arabic language, and it aims to give a new vision about the subject from the point of view of pragmatism ,And we found that the subject’s lesson in Arabic grammar is rich in its structural aspects that deserve to be re-described in light of the pragmatic vision. And we mention among them, his position as a grammatical subject in the propositional content of the speech act, And also his pragmatic referral function from the perspective of John Searle and functional grammar, he grammatical subject in Arabic comes in the form of a common noun, a proper noun, a demonstrative, a definite description, advanced name, late name, deleted name, a definite noun…etc Accordingly, the grammatical features that characterize the grammatical subject in Arabic would enrich the pragmatic lesson in theory and practice, and open the horizons of textual interpretation.